Putting the Pieces Together: Completing the Mechanism of Action Jigsaw for Sipuleucel-T. (7th March 2020) - Madan, Ravi A; Antonarakis, Emmanuel S; Drake, Charles G; Fong, Lawrence; Yu, Evan Y; McNeel, Douglas G; Lin, Daniel W; Chang, Nancy N; Sheikh, Nadeem A; Gulley, James L
Abstract: Sipuleucel-T is an autologous cellular immunotherapy that induces an immune response targeted against prostatic acid phosphatase (PAP) to treat asymptomatic or minimally symptomatic metastatic castration-resistant prostate cancer. In the phase III IMPACT study, sipuleucel-T was associated with a statistically significantly increased overall survival (OS) (median = 4.1 months) vs placebo. Patients with baseline prostate-specific antigen levels in the lowest quartile (≤22.1 ng/mL) exhibited a 13-month improvement in OS with sipuleucel-T. Together, this led sipuleucel-T to be approved and recommended as first-line therapy in various guidelines for treatment of metastatic castration-resistant prostate cancer. This review discusses the varied findings about the mechanisms of action of sipuleucel-T, bringing them together to form a more coherent picture. These pieces include inducing a statistically significant increase in antigen-presenting cell activation; inducing a peripheral immune response specific to the target (PAP) and/or immunizing (PA2024) antigens; stimulating systemic cytotoxic T-lymphocyte activity; and mediating antigen spread (ie, increased antibody responses to secondary proteins in addition to PAP and PA2024). Each of these pieces individually correlates with OS. Sipuleucel-T also traffics T cells to the prostate and is associated with long-term immune memory such that a second course of treatment induces an anamnestic immune response. Prostate cancer does not have a strongly inflamed microenvironment, thus its response to immune checkpoint inhibitors is limited. Because sipuleucel-T is able to traffic T cells to the tumor, it may be an ideal combination partner with immunotherapies including immune checkpoint inhibitors or with radiation therapy.